In situ growth of metal-free snowflake-like 1D/2D phosphorus element heterostructures for photocatalytic overall pure-water splitting. (13th October 2021) - Zhao, Ling; Fu, Hanping; Jian, Lishan; Zeng, Yating; Liu, Liran; Liang, Qingshuang; Xiao, Xiufeng
Abstract : In this work, we report a novel phosphorus element heterostructure with a snowflake-like morphology consisting of 1D rod-like black phosphorus (BP) and 2D flake-like red phosphorus (RP). Abstract : In this work, we report a novel phosphorus element heterostructure with a snowflake-like morphology consisting of 1D rod-like black phosphorus (BP) and 2D flake-like red phosphorus (RP). The content of black phosphorus in the heterostructure can be adjusted and the light absorption range and photocatalytic performance of the heterostructure increase with the proportion of black phosphorus. In this 1D/2D phosphorus element heterostructure, the photogenerated electrons in the conduction band of BP can be used for water decomposition to produce hydrogen, while the photogenerated holes in the valence band of RP can be used to produce oxygen, without using any sacrificial agents. The ratio of hydrogen and oxygen evolution rates is 2 : 1, and the rates are 2.0 and 1.1 μmol g −1 h −1, respectively. Therefore, we believe that this work demonstrates the potential of metal-free elemental photocatalysts with high efficiency, especially in overall pure-water splitting.